Plasma leyels of luteinizing and follicle stimulating hormones in naloxone-treated subestrus buffaloes - CHANDRASEKHAR, T; MADAN, M L (The Indian Journal of Animal Sciences, 2013)
To stude the effects of an antiopiate naloxone on hypophysial gonadotrophins; luteinizing hormone (LH) and follicle stimulating hormone (FSH) and estrus behaviour in subestrous buffaloes naloxone hydrochloride (1.5 mg/kg wt) dissolved in saline was infused into the jugular vein continuously for 4 hr through a catheter at a rate of 0.66 ml/min. Similarly, saline was infused 2 days before naloxone treatment. Blood sampling was done at 15 min interval during the infusion period and at hourly interval for 4 hr post-infusion in both the treatments. Mean LH levels measured showed a significant (P<0.05) increase during naloxone infusion compared to the levels observed during saline infusion. The pulse frequency and magnitude ofLH observed during the naloxone treatment were also significantly high (P<0.05 and P <0.01 respectively) compared to those in saline treatment. Mean LH levels post-infusion did not differ between treatments. Mean FSH levels measured in plasma samples did not show any significant difference between treatments during both infusion and post-infusion. Buffaloes though exhibited estrus after naloxone treatment, the cycle lengths were longer. The results showed that naloxone can increase LH levels for short periods and its effects on estrus need further investigation.